Phytobiotic activity of piper auritum and ocimum basilicum on avian E. Coli - Aguilar-Urquiso, Edgar; Itza Ortiz, Mateo Fabian; Sanginés-García, José Roberto; Pineiro-Vázquez, Angel Trinidad; Reyes-Ramirez, Arturo; Pinacho-Santana, Beatriz (2020)
Natural antimicrobials, known as phytobiotics, are used in bacterial infections. The objective of this study was to evaluatethe phytobiotic activity, in vitro and in vivo, of an extract and an essential oil of Piper auritum and Ocimum basilicum on avian Eschericia coli serotype O2 in broiler chickens experimentally infected. For the in vitro test, extracts at 4, 8, 12 and 16% in water-based solvent or alcohol at 70% were prepared from leaves of both plants. In the essential oils, solvents at 10% were used. A concentration of 1×108 CFU mL-1 of bacteria was seeded and on each sense disc, 25 μL of the extract or essential oil were poured, except on the positive or negative control. The diameter of the inhibition zone (DIZ) of bacterial growth was measured. In the in vivo test, 40 chickens were inoculated, by intratracheal route, with a bacterial suspension of 1 × 108 CFU mL-1. E. col was identified and isolated from the organs; mortality, morbidity and relative weight of the organs were measured, and postmortem lesions and histopathologic findings were observed. A completely randomized design and the Kruskal-Wallis test for data analysis was used. By increasing the concentration of the extract, DIZ was greater; at the time of slaughter, differences in body weight (p<0.05) were found and the majority of lesions were observed in lungs. It is concluded that leave extracts of P. auritum and O. basilicum had phytobiotic activity on E. col serotype O2.